Study on Stability of Tunnel Surrounding Rock and Precipitation Disaster Mitigation in Flowing Sand Body. (14th December 2021) - He, Yongyi; Sun, Bole; Wang, Mingnian
Abstract : Flowing sand is a special surrounding rock encountered by tunnel construction. Due to the looseness and low viscosity of the flowing sand, after excavation, the sand body is easy to flow along the open surface. In addition, the water seepage also causes tunnel instability. Considering the characteristics of water seepage, how to improve the stability of flowing sand bodies and prevent the instability of surrounding rocks has become a difficult problem. In this paper, a parametric experiment on the surrounding rock taken from the project site was carried out, and then, a numerical simulation of the flowing sand body was conducted to study the precipitation construction method and stability of the flowing sand body. Other than that, the tunnel face vacuum dewatering, vertical vacuum dewatering at the top of the tunnel, and the vacuum dewatering technology of the gravity well in poor geological section were systematically analyzed in our research. A radial vacuum enclosed precipitation process for the face of the tunnel was proposed, which effectively solved the problem concerning continuous seepage of water in the front. Through numerical simulation and field experiments, the basis for determining the precipitation parameters of the tunnel face was obtained, while aiming at the top position of the tunnel, a vertical vacuum negative pressure precipitation method of intercepting the top seepage water and the water supply behind the top of the tunnel was proposed. For the bottom of the tunnel, setting gravity wells on the side walls for the purpose of preventing seepage at the bottom was put forward. The application of these methods in the project ensured the safety of construction and improved the construction schedule. After the completion of the dewatering construction, the method of inserting plywood into the small pipe was adopted to avoid the collapse of the dry sand. Then, to solve the problem of borehole collapse in flowing sand bodies, pipe feeding was introduced, thus further enhancing the precipitation effect. Furthermore, in view of the problem that the dewatering hole in the flowing sand body is easy to collapse, resulting in the failure of 60% of the dewatering hole and the sand body is extracted from the dewatering pipe, causing the risk of the cavity at the top of the tunnel, a method of pipe following is presented to avoid the damage of geotextile caused by directly inserting the dewatering pipe and further improve the dewatering effect. All the above processes together form an omnidirectional three-dimensional negative pressure precipitation method that considers the special sand body flow and water seepage of unfavorable geology and that has been proved to enhance the stability of surrounding rock in practice.